KARAKTERISTIK PENUMPANG DAN PERJALANAN PADA KA PENUMPANG EKONOMI DI WILAYAH GERBANGKERTOSUSILA - Hitapriya Suprayitno; D. Irlambang D. Irlambang; Y.A. Pramono; A.G. Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2006)
Transportation system planning has to be regularly reviewed in order to meet the regional development. The transport user and their trip characteristics are very important parameters in transportation planning This paper presents both characteristics for Gerbangkerto susila economic class ' train. An interview survey was conducted to the passengers during the peak morning hour for all Gerbangkertosusila economic class trains for obtaining transport user and their trip characteristics. The results showed that the passengers comprised 67% male, 62% were of 21 — 40 years of age, 44% were senior high school graduates, and 33% were private sector employees. Based on the trip purpose, most of the passengers used the train for reaching their working base (41.2%). According to the embarkation base, about 8,6% of the passengers were coming from their residences. In addition, the destination of the passengers was mainly for returning home (34%). About 42.80% of the passengers were travelling 5 times a week.